Syntheses, Characterization and Properties of Open-Chain Copper(I) Complexes - Utz, Diana; Kisslinger, Sandra; Heinemann, Frank Wilhelm; Hampel, Frank; Schindler, Siegfried (European Journal of Inorganic Chemistry, 2011)
The coordination chemistry of copper complexes with the ligand L(1) [L(1) = 7E-N(1)-benzylidene-N(2)-(E)-2-(benzyl-ideneamino)ethyl]ethane-1,2-diamine] has been investigated. For copper(I) complexes of L(1), the counterion determines the molecular structure in the solid state. The reaction of [Cu(CH(3)CN)(4)]PF(6) with L(1) yielded the mononuclear complex [Cu(CH(3)CN)]PF(6) (1), whereas dinuclear helical [Cu(2)(L(1))(2)](ClO(4))(2) (2) resulted from a similar reaction with [Cu(CH(3)CN)(4)]ClO(4). Both compounds have been structurally characterized, and their solution behaviour investigated. Structurally characterized [Cu(L(1))(PPh(3))]ClO(4) (3) has been synthesized by reacting 2 with PPh(3). Exposure of a solution of 1 towards dioxygen in CH(3)OH and CH(2)Cl(2) yielded the dinuclear complexes [Cu(2)(L(1))(2)(OCH(3))(2)](PF(6))(2) (4) and [Cu(2)(L(1))(2)(OH)(2)](PF(6))(2) (5), respectively. Both compounds have been fully characterized. During the oxidation reaction, no hydroxylation of L(1) occurred. The oxidation reaction of 1 has been studied by a chemical approach and by UV/Vis spectroscopy, indicating the formation of a peroxido-bridged species during the reaction. Furthermore, by reduction of the imine groups in L(1) the ligand L(2) [L(2) = N(1)-benzyl-N(2)-[2-(benzylamino)ethylethane-1,2-diamine] was obtained and the dinuclear copper(II) complex [Cu(2)(L(2))(2)Cl(3)]PF(6)center dot 2MeOH (6) has been structurally characterized.
Keywords: Copper; Macrocycles; Oxidation; Oxygen; Helical structures; Anion effect